THE REPRESENTATION OF CHINESE CULTURAL VALUE FROM MAJOR CHARACTER IN KEVIN KWAN’S CRAZY RICH ASIAN NOVEL - Muhammad Alkautsar Nadi; Muhammad Fithratullah; Elizabeth Ngestirosa EWK (Journal of English Language Teaching and Learning, 2022)
AbstractThis research considered relevant to create understanding on the existence of diversity and tolerance, due to the existence of racism and Chinese as the largest population both in the US and the world have given a significant influence. The aim of this research is to expose the representation of Chinese cultural values reflected through major character in Kevin Kwan’s Crazy Rich Asian Novel. Chinese as the largest Asian immigrant in the US have influenced to the culture and society of America. They might move to other place in the world but they never forget their roots, culture and identity which is represented through literary works. The values are highlighted by revealing code, sign and symbols using representation theory by Stuart Hall as approach and semiotic theory by Roman Jakobson for its interconnection to structuralism. This thesis using descriptive qualitative method which giving the writer to have free access in interpretating the code, sign and symbols. Finally this research highlight four principles of Chinese values such as:  Orientation of Past Time, Respect for the hierarchy, Interdependence and Group orientation. Those values are represented though dialogue and narration highlighting characters in the novel the action, conversation, perspective and characteristic referring to Chinese values. Finally, it is proven that the novel is representing Chinese cultural values through its major Characters. Keyword: Chinese Values, Representation, Chinese American, Crazy Rich Asian